A comparison of the hematogenous cell infiltrate evoked by lymphokine injection with that of delayed hypersensitivity reactions. - Franco, M. F. (1978)
Lymphokine preparations of high potency obtained by in vitro assay were employed in vivo to determine whether they could produce inflammatory responses showing a cellular infiltrate that qualitatively or quantitatively resembled responses of delayed hypersensitivity. Hematogenous cell infiltrates in guinea pig skin were characterized in terms of the number and types of participating cells following intradermal injection of either lymphokines or an antigen (PPD) to which the animals exhibited delayed hypersensitivity. The dose of lymphokine or PPD per skin test site was selected on the basis of comparable ability to enhance vascular permeability. Delayed hypersensitivity responses showed, as expected, a persistent mononuclear cell exudate both in dermis and subcutis, but most notable in the dermis, during the 24 hours following antigen injection. In contrast, the response to lymphokine over the same period was characteristically neutrophilic and principally in the subcutis. There was no pronounced mononuclear cell infiltrate at any time throughout the reaction to lymphokine. It is concluded that preformed lymphokine produces a pattern of increased vascular permeability appropriate to a mediator of delayed hypersensitivity reactions, provided there is sustained secretion of this material. The ability of lymphokine to cause carbon labeling of dermal capillaries is also pertinent to a mediator of delayed hypersensitivity. The absence of significant mononuclear cell accumulation suggests that the in vitro chemotactic activity of lymphokine toward mononuclear cells may be more important for retention of mononuclear cells in the extravascular connective tissue space than for their selective accumulation.